Religiosidade e modos de vida : a (re)construção do lugar na comunidade rural Tenda do Moreno em Uberlândia - MG - Andrade, Rodrigo Borges de (2007)
In this work focused on analyzing the process of creation and reorganization of the place, from the lifeworld of the small agricultural producers of the community located in the municipality of Uberlândia-MG, Brazil, called Tenda do Moreno. The research ttok into consideration the customs, cultural and religious practices, and even the social relations, which occur during agricultural production, of the farmers of this community. The broad objective of this research is to analyze how the place was created in addition to, the social and cultural factors that permit such a community to perpetuate in the setting of the 21st century. The first settlers to this region were farmers who came in the beginning of the 19th century. The first farms were owned by many farmers in order to lower the costs. As time went by these farms in this region became agricultural neighborhoods, which eventually became the Tenda do Moreno community. The social content of this place was greatly influenced by the religiosity of their way of life, therefore, the social and cultural practices, which were permeated by moral and religious values, encouraged the sociability and reciprocity between the inhabitants. The social relations, which occurred during agricultural production, for example, were based on cooperation between the farmers, instead of competition. The production of the farm was measured by the increase of the quality of life of the inhabitants of the community, while the surplus production was directed towards the generation of more funds. Nevertheless, this reality was changed, during the 1980 s, due to the modernization of the agricultural practices in the municipality of Uberlândia and the increase in demand of urban consumer markets for agricultural products. These two factors forced these agricultural communities to abandon their traditional agricultural practices and become specialized in the production of one specific product. Although they were forced to abandon subsistence farming, they were able to maintain most of their customs, cultural traditions, religious practices, and even social relations. This environment is complex because the agricultural activities are modern, but the social, cultural and religious traditions are still grounded to the traditions of the founders of the place. One of the means that is used to preserve the link to the traditional customs is through religious celebrations that occur annually. These events allow the population to get to experience the lifestyle, customs, practices, and beliefs of their ancestors. The most important of these religious celebrations is the party of São José do Moreno. Currently, this religious celebration, which is conducted by the population of the community, has the intention of connecting the population to the traditions of the past and enabling the socialization between them. Furthermore, these social events are able to create a pleasant living environment that promotes a stable, balanced and deep-rooted community.